2017
DOI: 10.1097/cad.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid induces G1 phase arrest and apoptosis of triple-negative breast cancer cell MDA-MB-231 via p38 mitogen-activated protein kinase/p21/p27 axis

Abstract: Gallic acid (GA) possesses potential antitumoral activity on different types of malignancies. In this study, we aimed to explore the antitumoral effects of GA on triple-negative breast cancer (TNBC) cells, the breast cancer cells showing resistance to hormonal therapy or HER2 receptor targeting therapy. We observed that GA treatment significantly decreased the cell viability of human TNBC cell line MDA-MB-231 and HS578T in a dose-dependent manner. In addition, GA exerted a relative lower cytotoxicity on noncan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…Studies have shown that GA is effective in the treatment of pancreatic, colon, breast and melanoma cancers [16,[41][42][43]. Here, our results indicate that GA has cytotoxicity against A375 and MDA-MB-231 cell line and the IC 50 for melanoma A375 cell line is higher than and MDA-MB-231 cell line and other cell lines which previously reported.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have shown that GA is effective in the treatment of pancreatic, colon, breast and melanoma cancers [16,[41][42][43]. Here, our results indicate that GA has cytotoxicity against A375 and MDA-MB-231 cell line and the IC 50 for melanoma A375 cell line is higher than and MDA-MB-231 cell line and other cell lines which previously reported.…”
Section: Discussionsupporting
confidence: 80%
“…A number of previous studies demonstrated that cell cycle arrest and apoptosis may be directly associated (32)(33)(34). For instance, the apoptotic cascade may be inhibited or induced via cell cycle manipulation depending on the cellular circumstance (35).…”
Section: Discussionmentioning
confidence: 99%
“…The ROS-dependent pro-apoptotic effects of GA were also demonstrated in declined viability of HCT-15 colon cancer or LNCaP prostate cancer cells [27]. The beneficial effects of GA in triple-negative breast cancer (TNBC) were suggested by the study that revealed an ability of GA to induce G1 phase arrest and apoptosis via p38 mitogen-activated protein kinase/p21/p27 axis in MDA-MB-231 cells [35]. Moreover, GA was associated with p53-involved upregulation of Fas, FasL, and DR5 and apoptosis in AGS cells [36].…”
Section: Gallic Acidmentioning
confidence: 97%